Sustentabilidade nas etapas da construção civil - Carvalho, Liandra Melo (Universidade Federal Rural do Semi-Árido, 2019)
Nowadays we live a development model based on high consumption of natural resources and consequent environmental degradation, from this scenario the need arises to make society aware that a new model of sustainable development directed to the civil construction area is possible. With this, the elaboration of this research was done through a bibliographical study focused on the sustainability theme in the civil construction stages. Faced with the confrontation of the idea of the selected authors, it was possible to understand that, in order to achieve a sustainable proposal in Brazil, policies and legislation are needed to regulate the use of sustainable materials in civil constructions.
Monografia
Keywords: Edifício; Projeto; Sustentável; Buildings; Project; Sustainable; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA